The making of another major motion picture masterpiece eaudiobook A novel. - Hanks, Tom (Books on Tape, 2023)
From the legendary actor and best-selling author: a novel about the making of a star-studded, multimillion-dollar superhero action film...and the humble comic books that inspired it. Funny, touching, and wonderfully thought-provoking, while also capturing the changes in America and American culture since World War II. "Wild, ambitious and exceptionally enjoyable." —Matt Haig, best-selling author The Midnight Library, The Humans and Reasons to Stay Alive Part One of this story takes place in 1947. A troubled soldier, returning from the war, meets his talented five-year-old nephew, leaves an indelible impression, and then disappears for twenty-three years. Cut to 1970: The nephew, now drawing underground comic books in Oakland, California, reconnects with his uncle and, remembering the comic book he saw when he was five, draws a new version with his uncle as a World War II fighting hero.  Cut to the present day: A commercially successful director discovers the 1970 comic book and decides to turn it into a contemporary superhero movie. Cue the cast: We meet the film’s extremely difficult male star, his wonderful leading lady, the eccentric writer/director, the producer, the gofer production assistant, and everyone else on both sides of the camera. Bonus material: Interspersed throughout are three comic books that are featured in the story—all created by Tom Hanks himself—including the comic book that becomes the official tie-in to this novel’s "major motion picture masterpiece." *Includes a downloadable PDF of the comics from the book and a QR code for access to the original screenplay of Knightshade: The Lathe of Firefall